O cárcere feminino brasileiro e seus aliados: abandono, violência simbólica e institucional - Sousa, Célia Regina Nilander de (2021)
Women raped in life and in prison. The weight of patriarchy and gender inequality accompanies women throughout their lives. In prison, an ingredient that potentiates the violence suffered is present: the breaking of imposed social standards. This factor, added to the stigma of “delinquent” and to spatial confinement, generate existential impoverishment, excluding and generating “hypervulnerability”. Triple punished, the imprisoned female reaps the bitter taste of abandonment and the excruciating pains of prison. Inhuman and cruel punishments are not allowed in the Brazilian legal system, but state violence imposes itself on Human Dignity and commands the monopoly of violence when imprisoning women in prisons made for men, when it makes unfeasible and/or difficult to see in prison, when it denies products basic intimate hygiene, in fact, menstrual poverty goes beyond the scarcity of intimate products for women, which directly affects human rights. This study reveals the drastic consequences of patriarchy and the abandonment of incarcerated women, implacable consequences in life outside the walls, leading “delinquent” women to a “death penalty” in life